Maqasid Sharia-based Frugal Living: A Phenomenological Study of IEKI Students - Haq, Zulfa Naurul; Ramdani, Isra Muhamad; Nauval Syafik Hasim; Aditia Arif Firmansyah; Ditianisya Syarif (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2026)
Macroeconomic pressures and modern consumerism trends have made Muslim youth interpret frugal living pragmatically and often ignore spiritual values. Thus, the research focuses on the application of frugal living in the Islamic Economics and Finance student environment as a form of Maqashid Sharia values, especially the principle of hifdzu al-mal. The method applied is in the form of a phenomenological qualitative approach to explore in depth the essence of the participants' life experiences. The data was obtained through in-depth interviews with 16 students of the 2022-2025 batch determined through judgment sampling. Thematic analysis is applied to identify patterns of meaning that ultimately reveal four aspects, namely intellectual, integration of findings, strategies, and behavior. The results of the research concluded that there is a phenomenon of "Academic-Spiritual Habituation". This phenomenon shows that students' Islamic economic literacy is not just a theory, but transforms into an effective self-control mechanism to fortify them from modern consumption culture. It is this awareness that ultimately transforms the frugal lifestyle from just a financial trend to a form of worship and a tangible manifestation of faith in their daily lives.